(untitled) (Journal of the College of Basic Education, 2022)
The energy transfer of fluorescence resonance in aqueous solution was studied between two organic dyes, Fluorescein and Rhodamine B. Both dyes were found in solution as monomers, according to spectroscopic studies. Energy transfer was observed in fluorescence resonance imaging solutions containing fluorescein and rhodamine B. with different concentrations of the acceptor RhB dye in the range of (1.5×10-5 M to 3.5×10-5M). Studies using Both UV–vis absorption and fluorescence spectroscopy demonstrated that the two dyes, when dissolved in solution, appear largely as monomers.